Mothers’ Behaviour on the Provision of Snack which Risk of Children’s Health - Ronasari Mahaji Putri; Novita Dewi; Neni Maemunah (Jurnal Keperawatan, 2020)
Introduction:Many foods circulating in the community do not meet the healthy snack food criteria. Many children tend to consume unhealthy snacks. Provision of snack food by the mother as a regulator of family consumption determines the type of snack food consumed by children. Objective:This study aims to determine the description of the provision of snack food for children who are at risk of child health by housewives. Method:This research is a descriptive study with the population is all mothers who have children under five in the Posyandu Guyup Rukun RW.05 Klojen Penanggungan East Java with samples taken with a total sampling technique of 41 people. The variable in this study is the provision of snack food. The instrument used was a checklist sheet and a snack food consumption sheet in terms of type and frequency. Data analysis using multivariate analysis. Result:The results revealed that most of the mothers behaved in providing snacks as requested by children on television, did not provide healthy provisions, did not provide pocket money and tended to provide snacks that were at risk for children's health, namely tempura sausage, chicken nuggets, fried noodles and not providing drinks that healthy as fruit juice as a child's snack food.Discussion: The importance of education about healthy and safe snacks for school-age children.